Need Analysis of English for Mechanical Engineering - Dewanti Ratna Pertiwi; Maria Asumpta Deny Kusumaningrum (Universitas Ahmad Dahlan, 2019)
To conduct an ESP instructional program, it is important to analyze the current situation of the students and the objectives of the program. This study explored the need analysis of English for mechanical engineering at Adisutjipto college of technology, Yogyakarta. This department offers aircraft maintenance, manufacture and material, and energy conversion majors that require the English instruction covers the needs of those concentrations. The data were collected from the students, lecturers, tracer study, and academic affair officers by distributing questionnaire, interviewing, and observing the classroom activities. The finding showed that the compositions of the three concentrations and should involve aerospace engineering materials, the presentation of the materials should focus on the language skills development based, the teaching technique should involve classroom and digital instructions and the instruction should be outcome based education (OBE).Â Â Â Keywords: need analysis, ESP, mechanical, aerospace, engineering